Wounded healer therapists: A legacy of developmental trauma - Bond, Pat (European Journal for Qualitative Research in Psychotherapy, 2020)
My research asks, ’what impact might a personal history of complex developmental trauma have on a counsellor’s experience of, and work with, traumatised clients?’ Semi-structured interviews were conducted with 6 experienced therapists who had self-identified as having been traumatised as children. A seventh contribution is a reflective narrative of my own story. Three of the themes which emerged in a phenomenologically orientated qualitative bricolage were: help-seeking, trauma treatments, and survival strategies. The analysis uncovered considerable diversity of both narrative and meaning-making, even in this small sample of participants and this was reflected in the participants’ diverse beliefs about what constitutes effective practice in trauma therapy. Their experience challenges the espousal of standard treatment protocols seen in some primary care and substance abuse services and calls for greater flexibility in both practice and research strategy. Discussion is offered around diversity, research approaches, and the use of personal experience in the therapy room which have implications for therapist training, therapist self-care, therapeutic strategies, and further research.